Comparative Advertising and Competition Policy - Francesca Barigozzi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2004)
Only recently, competition authorities tend to agree on comparative advertising being helpful in promoting competition. They now encourage firms to use it. They reason that comparative advertising, if fair and not misleading, increases consumers' information about alternative brands. For this to work, comparative claims must be credible. Competition policy and legal practice are essential in making comparative advertising (directly and indirectly) informative. In this paper, first we provide a legal background of comparative advertising in in Europe and the US. Second, we provide an economic analysis of comparative advertising. Here, we discuss the ways comparative advertising can affect market outcomes. Third, we provide an analysis of some recent legal cases in Europe and the US. Overall, we focus on the scope of information transmission through comparative advertising and on the way antitrust laws affect it.
Keywords: 330; Vergleichende Werbung; Wettbewerbspolitik; Wettbewerbsrecht; USA; EU-Staaten